Qualitative Analysis Of Nutrition Management Of Stunting Toddlers in The Work Area Of Jabung Public Health Center - Raden Maria Veronika Widiatrilupi; Retno Dewi Prisusanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Efforts in the context of the acceleration action plan One way to improve nutrition is to tackle stunting in toddlers, focusing on the First 1000 Days Life (HPK) or SUN ( Scaling Up Nutrition ). Stunting is the highest prevalence in the Jabung Health Center work area in Malang Regency , This show that quality service health is still low. The purpose of this study was to evaluate the management of nutritional status of stunted toddlers with input, process and output elements. This study is a qualitative study. Initial informants were determined using purposive sampling techniques. Data collection methods through interview deep, observation And documentation to 6 informant beginning Which consists of from head health center, midwife coordinator KIA, coordinator nutrition, midwife village, cadre And Mother toddler target. Two informant triangulation Which consists of from coordinator health family And coordinator nutrition Service Health Regency. Results study show on stage input that is power health Which involved Still need addition, Not yet There is power nutrition. On element process, part program implemented with Good covering program Healthy for woman pregnant, giving breast milk Exclusive, monitoring grow flower, giving additional food, giving vitamin A except for the program of giving sprinkles. In the elements output, coverage prevalence stunting in Health Center Jabung Regency Poor year 20 23 as big as 1 7 , 8 4 %.